The petroglyphs and pictographs of Missouri - Diaz-Granados, Carol, 1943- (University of Alabama Press, 2000)
"This book documents Missouri's rich array of petroglyphs and pictographs, analyzing the many aspects of these rock carvings and paintings to show how such representations of ritual activities can enhance our understanding of Native American culture." "Missouri is a particularly important site for rock art because it straddles the Plains, the Ozarks, and the Southeast. Carol Diaz-Granados and James Duncan have established a model for analyzing this rock art as archaeological data and have mapped the patterning of 58 major motifs across the state. Of particular importance is their analysis of motifs from Mississippi River Valley sites, including Cahokia." "The authors include interpretive discussions on iconography and ideology, drawing on years of research in the ethnographic records and literature of Native Americans linguistically related to earlier peoples. Their distribution maps show how motifs provide clues to patterns of movement among prehistoric peoples and to the range of belief systems. By documenting these fragile images, this book makes a major contribution to rock art research in North America."--Jacket